PENERAPAN E-LEARNING MELALUI PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA - Glory Indira Diana Purba (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to determine whether the application of e-learning in problem-based learning can improve the problem solving abilities of FMIPA Unimed students. The approach used in this research is descriptive qualitative research by actively involving through e-learning the actors in the learning process, namely lecturers and students, as well as other related subjects. This study's design consists of three stages: (1) the development of learning tools and research instruments, (2) the testing of learning tools and research instruments, and (3) the implementation of experiments. Keywords: Electronic Learning, Problem-Based Learning, Mathematica Problem Solving Ability